New cytotoxic compounds from Myristica fatua Houtt leaves against MCF-7 cell lines. (June 2017) - Fajriah, Sofa; Darmawan, Akhmad; Megawati; Hudiyono, Sumi; Kosela, Soleh; Hanafi, Muhammad
Graphical abstract: The phytochemical investigation of the Myristica fatua leaves yielded two novel compounds. A lignan, (7S, 8R, 8′S, 7′S) 7, 7′-bis(3-hydroxy-5-methoxyphenyl)-8, 8′-dimethylbuthane-7, 7′-diol (1 ), and a diaryl nonanoid, 3"-hydroxy demethyl dactyloidin (2 ) showed cytotoxic activity against MCF-7 cell lines. Highlights: Phytochemical investigation on Myristica fatua leaves led to the isolation of new lignan and dactyloidin derivatives. A lignan, (7S, 8R, 8′S, 7′S) 7, 7′-bis(3-hydroxy-5-methoxyphenyl)-8, 8′-dimethylbuthane-7, 7′-diol (1), and a diaryl nonanoid, 3"-hydroxy demethyl dactyloidin (2) were assayed using MCF-7 cell lines. These compounds were shown to have potential anti breast cancer activity. Abstract: Two novel compounds, (7S, 8R, 8′S, 7′S) 7, 7′-bis(3-hydroxy-5-methoxyphenyl)-8, 8′-dimethylbuthane-7, 7′-diol, and 3"-hydroxydemethyldactyloidin were isolated from the leaves of Myristica fatua Houtt, and their structures were determined using spectroscopic techniques, including 2D NMR. Both compounds showed in vitro cytotoxic activity against the breast cancer cell line MCF-7, with IC50 of 26.19 and 8.33 μM, respectively.